Impact of PROGRESA on school attendance rates in the sampled population - Schultz, T. Paul (International Food Policy Research Institute, 2000)
This report on school attendance patterns adopts the same conceptual framework as a previous report on enrollment, and explores whether the Progresa program had an additional impact on variation in school attendance rates in the school year 1998/99 compared to the attendance recorded in the survey collected in March 1998 before Progresa identified beneficiaries and began the educational grants to encourage enrollment and attendance among children in poor households. The earlier study was entitled Progresa’s Impact on School Enrollments from 1997/98 to 1998/99, by the same author.